A new basal ornithuromorph bird (Aves: Ornithothoraces) from the Early Cretaceous of China with implication for morphology of early Ornithuromorpha. (January 2016) - Wang, Min; Zhou, Zhonghe; Zhou, Shuang
Abstract : Ornithuromorpha is the most derived avian group in the Early Cretaceous, advanced members of which encompass all living birds (Neornithes). Here we report on a new basal ornithuromorph bird, Bellulia rectusunguis gen. et sp. nov., represented by a nearly complete skeleton from the Early Cretaceous Jehol Biota in northeastern China. A comprehensive phylogenetic analysis resolved the new taxon in a basal position that is only more derived than Archaeorhynchus and Jianchangornis among ornithuromorphs, increasing the morphological diversity of basal ornithuromorphs. The new specimen has a V‐shaped furcula with a short hypocleidium, a feature otherwise known only in Schizooura among Cretaceous ornithuromorphs. We discuss the implications of the new taxon on the evolution of morphology of primitive ornithuromorphs, particularly of pectoral girdle, sternum and limb proportion pertaining to powered flight. The preserved gastroliths and pedal morphology indicate herbivory and lakeshore adaption for this new species. © 2015 The Linnean Society of London